(untitled) (Revista Brasileira de Computação Aplicada, 2018)
Even treatable and preventable with medication, tuberculosis (TB) continues to infect and cause deaths globally, especially in the poorest countries and in most vulnerable areas of the rich countries. Given this situation, the study of the growth curve of Mycobacterium tuberculosis, which causes tuberculosis, can be a strong ally against TB, helping in the development of new drugs or for the development of the theory. This paper describes a study of the Mycobacterium tuberculosis growth curve and it aims to test hypotheses on data obtained by agent-based simulation with the population mean observed in an experiment in vitro. The tested hypotheses compare the mean of experiments for the first hour of the day. The tests were performed using the Student distribution. We believe that our approach, that use agent-based model, could reproduce Mycobacterium tuberculosis growth curves.